Fragile X Mental Retardation Protein Mediates the Effects of Androgen on Hippocampal PSD95 Expression and Dendritic Spines Density/Morphology and Autism-Like Behaviors Through miR-125a - Chen, Huan; Qiao, Dan; Wang, Chang; Zhang, Bohan; Wang, Zhao; Tang, Longmei; Wang, Yibo; Zhang, Ran; Zhang, Yizhou; Song, Leigang; Zuo, Hongchun; Guo, Fangzhen; et al. (Frontiers in Cellular Neuroscience, 2022)
Dysregulated synaptic plasticity is a key feature of neurodevelopmental disorders, including autism. This study investigated whether Fragile X mental retardation protein (FMRP), a selective RNA-binding protein that regulates synaptic protein expression by interacting with miRNAs, mediates the effects of androgens that play an important role in regulating the synaptic plasticity in the hippocampus. Experiments using mouse hippocampal neuron HT22 cells demonstrated that dihydrotestosterone (DHT) increased the expression of postsynaptic density protein 95 (PSD95) by inhibiting FMRP expression. Administration of miR-125a inhibitor upregulated the expression of PSD95 and significantly affected the DHT-induced upregulation of PSD95. FMRP knockdown in HT22 cells reduced the expression of miR-125a. Moreover, miR-125a inhibitor upregulated the PSD95 expression in the DHT-treated HT22 cells with FMRP knockdown. Subsequently, the effects of androgen-mediated via FMRP in regulating neural behavior and synaptic plasticity were investigated using Fmr1 knockout (KO) and wild-type littermate (WT) mice. The castration of WT mice reduced the androgen levels, aggravated anxiety and depression, and impaired learning and memory and sociability of mice. DHT supplementation post-castration reversed the alterations in density and maturity of dendritic spines of hippocampal neurons and behavioral disorders in WT mice; however, it did not reveal such effects in Fmr1 KO mice. Further, immunohistochemical staining and western blotting analyses after knocking down miR-125a revealed similar effects of castration and post-castration DHT supplementation on PSD95 protein expression. These findings clarified that FMRP mediated the effects of DHT through miR-125a in regulating the expression of hippocampal synaptic protein PSD95. This study provides evidence for the neuroprotective mechanism of androgen in synaptic plasticity and suggests that treatment interventions with androgen could be helpful for the management of synaptic plasticity disorders.